Radionuclide diagnosis of Meckel’s diverticulum: A case report - Dhima, Arben; Trushaj, Esilda; Blloshmi, Amarildo (ESI Preprints (European Scientific Journal, ESJ), 2025)
Introduction: Meckel's diverticulum is a common congenital anomaly of the small intestine that results from the incomplete obliteration of the vitelline duct (omphalomesenteric duct). The most common symptom leading a patient to the emergency department is painless gastrointestinal bleeding. The most sensitive diagnostic test is the Meckel radionuclide scan using 99mTc-pertechnetate, commonly known as the Meckel scan. This case report presents an 18-year-old patient who came into the emergency department with gastrointestinal bleeding and was diagnosed with Meckel's diverticulum using Meckel scan. Methodology and Discussion: An 18-year-old male patient presented to the emergency department with hematochezia, several days of abdominal pain, nausea, and vomiting. After clinical assessment and objective examination, several tests were conducted, all of which returned normal results. The clinical suspicion pointed towards Meckel's diverticulum. The diagnosis was confirmed with a simple examination: scintigraphy, a nuclear imaging method in which technetium-99m is injected and absorbed by the mucous-producing cells of the ectopic gastric mucosa. The patient underwent laparotomy and the histopathological examination confirmed the diagnosis of Meckel's diverticulum. Conclusion: Scintigraphy is the appropriate diagnostic modality in cases of unexplained gastrointestinal bleeding when Meckel's diverticulum is suspected. This radionuclide scan has very high specificity and sensitivity when performed according to protocol. Additionally, it is a low-cost examination with lower radiation exposure compared to other imaging modalities.